2002
DOI: 10.1152/japplphysiol.00627.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on mRNA expression of select adrenal medullary catecholamine biosynthetic enzymes

Abstract: The effect of submaximal endurance training (SET) on sympathoadrenal activity is not clear. We tested the hypothesis that SET (90 min/day, 5 days/wk, for 12 wk) elevates mRNA expression of catecholamine (CA) biosynthetic enzymes, tyrosine hydroxylase (TH) and dopamine-beta-hydroxylase (DbetaH) in the adrenal medullae of adult, female Sprague-Dawley rats. SET increased TH protein level by 35%, TH activity by 62%, TH mRNA expression by 40%, and DbetaH mRNA expression by 67%. In addition, we examined the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…To reveal the detailed mechanisms underlying age-and CR-related changes in adrenomedullary TH and DβH, we measured the binding activities of AP-1 and CREB transcription factors in nuclear extracts from adrenal medulla, since AP-1 and CREB play a central role in the regulation of TH and DβH expression during stress (Sabban et al, 2004a(Sabban et al, , 2004bSabban and Kvetnansky, 2001) and forced exercise training (Erdem et al, 2002b;Tumer et al, 2001). However, in the present study, we found that neither of these transcription factors is responsible for the observed changes in adrenomedullary TH and DβH levels with age or in response to CR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To reveal the detailed mechanisms underlying age-and CR-related changes in adrenomedullary TH and DβH, we measured the binding activities of AP-1 and CREB transcription factors in nuclear extracts from adrenal medulla, since AP-1 and CREB play a central role in the regulation of TH and DβH expression during stress (Sabban et al, 2004a(Sabban et al, , 2004bSabban and Kvetnansky, 2001) and forced exercise training (Erdem et al, 2002b;Tumer et al, 2001). However, in the present study, we found that neither of these transcription factors is responsible for the observed changes in adrenomedullary TH and DβH levels with age or in response to CR.…”
Section: Discussionmentioning
confidence: 99%
“…TH and DβH mRNA levels were determined using Northern blot analysis as previously described (Tumer and Larochelle, 1995;Erdem et al, 2002b). Briefly, total cellular RNA was extracted using Tri-reagent (Sigma, St. Louis, MO), and the isolated RNA was quantified by spectrophotometry.…”
Section: Th and Dβh Mrna Levelsmentioning
confidence: 99%
See 3 more Smart Citations